Metabolomic profiling of infants undergoing cardiopulmonary bypass and association with clinical outcomes: a systematic review - Leonardo Meggiolaro; Laura Moschino; Laura Moschino; Matteo Stocchero; Giuseppe Giordano; Vladimiro Vida; Giovanni Di Salvo; Eugenio Baraldi; Eugenio Baraldi (Frontiers in Cardiovascular Medicine)
IntroductionThe incidence of adverse short-term outcomes for infants who undergo complex congenital heart disease (CHD) surgery with cardiopulmonary bypass (CPB) is still high. Early identification and treatment of high-risk patients remain challenging, especially because clinical risk factors often fail to explain the different outcomes of this vulnerable population. Metabolomics offers insight into the phenotype of the patient and the complex interplay between the genetic substrate and the environmental influences at the time of sampling. For these reasons, it may be helpful to identify the mechanisms of physio-pathological disruptions experienced in neonates undergoing congenital heart surgery and to identify potential therapeutic targets.MethodsWe conducted a systematic review (PROSPERO: ID 565112) of studies investigating the association between targeted or untargeted metabolomic analysis of infants undergoing elective surgery with CPB for CHD and clinical outcomes. The PRISMA guidelines were followed. We searched MEDLINE via PubMed, EMBASE via Ovid, the Cochrane Central Register of Controlled Trials, the Cochrane Library, ClinicalTrials.gov and the World Health Organization's International Trials Registry and Platform.ResultsSeven studies involving 509 children (aged 1 day to 21.3 months), all of whom underwent cardiac surgery requiring CPB, were included for qualitative analysis. We found associations between metabolomic profiles and various clinical outcomes, such as mortality, acute kidney injury (AKI), and neurological outcomes. Specific metabolites (mainly amino acids, their metabolic products and fatty acids) were identified as potential biomarkers for these outcomes, demonstrating the utility of metabolomics in predicting certain postoperative complications.ConclusionThe quality of the evidence was limited due to heterogeneity in study designs and small sample sizes, but the findings are promising and suggest that further research is warranted to confirm these associations.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, PROSPERO ID 565112.